Plume moths in the protected areas of KwaZulu Natal province, Republic of South Africa - Kovtunovich, Vasiliy N.; Udovichenko, Pavel; Armstrong, Adrian; Streltzov, Alexander N.; Ustjuzhanin, Peter Ya (Ecologica Montenegrina)
The article gives 70 Pterophoridae species of nature reserves and national parks of KwaZulu Natal province, Republic of South Africa. New taxonomic combinations are revealed, new data on the distribution of Plume moths in the Republic of South Africa are indicated. New generic combinations were established for two species of Marasmarcha ammonias (Meyrick, 1909) and Sphenarches erythrodactylus (Fletcher, 1911). 7 species are recorded for the first time for the province of KwaZulu Natal.